Non-convulsive Status Epilepticus in Children, Electro-Clinical Profile and Response to a Specific Treatment Protocol (Bangladesh Journal of Child Health, 2010)
Objective: Non-convulsive status epilepticus (NCSE) is an under-diagnosedneurological condition. We report the electroclinical profile and treatment outcome ofchildren diagnosed with NCSE.Methods: Total 45 children were identified with NCSE at the EEG laboratory fromSeptember 2004 to January 2009. Their presenting complaints, past clinical andbirth related information were meticulously recorded. On diagnosis the referringphysicians were requested to repeat the test after starting treatment. Later they weretreated with a specific protocol on admission at the Neurology Unit of Dhaka ShishuHospital. Two lines of treatment with daily routine EEGs were introduced. Electroclinicaloutcome were recorded on discharge. The children are still on regular followup to record the long-time result of the protracted treatment.Results: Motor regression and postural problem were the primary complaints in themajority (37/45, 82%) followed by involuntary movement, muscle twitching, jerks orfrequent fall (31/45, 69%), speech regression (29, 64%) and change of usual behavior(25/45, 56%). Prior major seizures (generalized tonic clonic, tonic or clonic) wasreported in 32/45, 71%, within 1 week to 1 year. Initial diagnosis was multiple includinghysteric conversion reaction, post-ictal regression or neuro-degenerative disorder.None was suspected with NCSE. Diagnosis was confirmed by the EEG finding ofcontinuous generalized (82%) or localized (18%) slow spike-wave complexes. Onprotracted treatment, 82% achieved the target.Conclusion: NCSE is common in children, may occur de-novo. The variable phenotypemay lead to erroneous diagnosis. A protracted treatment protocol is suggested. Furtherreporting on this issue will help to assist the clinicians for early-diagnosis and treatment.Key words: non-convulsive status epilepticus; electro-clinical diagnosis; motorfunctional regression; speech regression; behavioural changes.DOI: 10.3329/bjch.v33i3.5689Bangladesh Journal of Child Health 2009; Vol.33(3): 90-99